Impact of Climate Change on Agricultural Growth in Nepal - Acharya, Shankar Prasad; Bhatta, Guna Raj (NRB Economic Review, 2013)
The concern of climate change has been emphasized in the field of economics too owing to the challenge of adapting to global warming for sustainable development and growth. This challenge becomes dominant in the developing economies like Nepal as these countries face the combination of equator vulnerable climate change pattern, agro-based economy, scarcity of resources, and lack of influence to put forth the global agenda of climate change to international forum. In this paper, we conducted a quantitative modeling of climate change and its impact to the agricultural value addition in Nepal taking into consideration annual series of agricultural gross domestic product (AGDP), rainfall, temperature, seeds and fertilizer distribution data for the period of 36 years ranging from 1975 to 2010. The statistical inferences show the significant positive impact of rainfall to the AGDP. Nevertheless, improved seeds and chemical fertilizers are found to be insignificant. The impact of rising temperature to AGDP is cautious as we find a large negative coefficient of cyclical component of temperature, but statistically insignificant. This insignificance may be due to the nature of very little temperature variability over the study period as compared to the variability in AGDP. The country should assess the impact of climate change in national, regional, and district level to collect the spatial information and underpin the adaptive policies to the required areas.